KEWENANGAN BIDANG PERTANAHAN DALAM PELAKSANAAN OTONOMI DAERAH - deliani, deliani (Politeknik Ganesha Medan, 2024)
Implementation of regional autonomy that is now almost up to enter the age of 10 years can reap a lot is said to have problems. One of the issues that must be addressed immediately is the problem of authority land. According to Law No. 5 th 1960, land is the task of the government (central government) while the provisions in Law No. 32 year 2004 field of land is the authority that has been submitted to the district / city. This course of action necessary for the second sincrinicity regulations are. Based on the approach to the legislation can be concluded that the authority has been the occurrence of land disputes as a result of dissincronicity regulations. For that they need to be made immediately the implementation of Tap MPR No. IX Th 2001 on Agrarian reform and the Management of Natural Resources in the Field of Land.